Islamic Moral Education and Character Building in the Era of IoT - Kurniawan, Wakib; Annisah, Siti (Institut Darul Falah Bandung Barat, 2025)
This study investigates the role of Akidah Akhlak teachers in shaping the noble character of students in the era of the Internet of Things (IoT), a time marked by rapid technological change and digital exposure. The research was conducted at MTs Bustanul ‘Ulum Jayasakti in Central Lampung using a descriptive qualitative approach. Data were collected through observation, interviews, and documentation. The findings show that teachers not only deliver religious content but also act as moral exemplars and digital mentors. They integrate Islamic values into students’ digital realities using contextual strategies such as role-modeling, project-based learning, and ethical digital supervision. Despite facing challenges like limited digital infrastructure and varying parental involvement, these educators effectively foster students’ character by aligning Islamic teachings with contemporary digital contexts. The study concludes that strengthening teachers’ digital literacy and pedagogical adaptability is crucial to preserving moral integrity in a digital society.